Intersetorialidade nas políticas brasileiras de saneamento e de recursos hídricos em um contexto de reformas - Ney Albert Murtha (2016)
The object of this thesis is to understand the forms of inter-sector cooperation between public policies in the water and sanitation and water resources sectors in Brazil. It examines how intersector cooperation happens within the scope of these policies, in a context of limited, unfinished reforms. We focus both on the reform of water resources policy, which does not live up to the expectations of breaking with the state-centered traditions of water management, and the policy reform in the water and sanitation sector, which clashes with the conservative and insular institutional environment inherited from PLANASA. The study draws on the neoinstitutionalist concept of path dependence to explore the institutional and political effects of past arrangements that impose conditions on current policies. In order to develop the work, I describe the two sectors and their policies, as well as their historical dynamics, exploring the main aspects of the rhetoric constructed around key concepts, as found in the policy-planning documentation of both areas. The thesis also includes a review of conceptual elements regarding policy integration and references to the analyses of specialists who cast light on those aspects that enhance or hinder inter-sector cooperation between these policies arenas. I interviewed a group of academic and government specialists in the aforementioned policies in order to explore their perspectives on inter-sectoral action and on recent historical processes. The narratives of these specialists and the results of the systematic documentary analyses carried out in the research, cast doubts on the actual reformist character of the policies implemented in the water and sanitation and water resources sectors. The lessons confirm that the discourse of inter-sector cooperation has little practical repercussion on these policies and that there is significant institutional continuity with the past